Usage of Social Media To Engage With Malaysian Youths Concerning Road Safety Awareness - Sinnappan, Santhidran; Veltri, Giuseppe Alessandro; Peter, Lunt; Periyayya, Thinavan (Journal of Contemporary Issues in Media & Communication (JCIMC), 2023)
Changing the behaviour of road users to safer drivers is a topic of great interest to researchers and policy makers. Behavioural economics asserts that behavioural decisions are based on heuristics or shortcuts rather than logical rationality due to various constraints. Nudging theory recognises that heuristic thinking is widespread and proposes to trigger the desired behaviour change with minimal visual and linguistic means. This study therefore focused on identifying specific types of nudges that can increase the salience and value of safe driving behaviour among young citizens in Malaysia aged 17 to 25. A preliminary thematic analysis using focus group discussions resulted in three main themes, namely family concern, positive affection for speed, and overconfidence. Positive affection was reinterpreted as a negative consequence and the final theme was overconfidence. Based on the three themes, relevant visual stimuli were created and tested in an online Facebook group experiment with 337 participants (N=337) in a pre-post-test design. Participants were asked to complete a safe driving attitude test at baseline and after three weeks. During this time, the three experimental groups were exposed to the visual stimuli via Facebook discussion. Results showed that concern for family was most significant, followed by overconfidence. Reframing was not significant. The results provide important information that can be used to prepare road safety campaigns that can produce positive behavioural changes related to safe driving.